Pattern of linear growth and progression of bone maturation for girls with early-onset puberty: A mixed longitudinal study - Liu, Shuangyi; Su, Zhe; Pan, Lili; Chen, Jinfeng; Zhao, Xiu; Wang, Li; Zhang, Longjiang; Su, Qiru; Su, Huiping (Frontiers in Pediatrics, 2023)
Background and objective. With a worldwide trend to earlier age of onset of puberty, the prevalence of early-onset puberty (EP) among girls has increased. The impact of EP on the pattern of linear growth and bone maturation is unclear. Accordingly, the objective of our study was to describe this pattern for girls with EP in Shenzhen, China. Methods. A total of 498 girls diagnosed with EP at Shenzhen Children's Hospital, China, and not treated with drug therapies, were enrolled into our study between January 2016 and December 2021. A total of 1,307 anthropometric measurements and 1,307 left-hand radiographs were available for analysis. Artificial intelligence (AI) was used to determine bone age (BA). Participants were classified into groups according to chronological age (CA) and BA. The pattern of linear growth (height) and progression of bone maturation progression was described between groups using the Lambda-Mu-Sigma (LMS) method. Published height-for-CA and height-for-BA norm references for healthy Chinese population were used for age-appropriate comparisons. Results. The mean CA of appearance of first pubertal signs (breast buds) was 8.1±0.5 years of age. Compared to norm-referenced data, girls with EP were notably taller at a CA of 7-10 years. This was followed by an attenuation in linear growth, with girls with EP generally reaching their predicted target adult height. From 7-10 years of BA, the linear growth was slower in the EP group compared to norm-reference values. This was followed by a period of catch growth at 11.2 years of BA, with growth curves approaching norm-referenced values. The BA progressed rapidly from 7-8 years of age in about half of the girls with EP (median ΔBA/ΔCA >1.9), slowing thereafter until the period of catch-up growth at 11.2 years of age. Conclusions. BA provides a more reliable reference than CA to assess growth parameters among girls with EP. Our data show that EP does not negative impact final adult height, generally. Therefore, the growth curves from our study are relevant, providing a reference and evidence for pediatricians to improve prediction of growth in this clinical population and, thus, prevent over-treatment.